A case Report: Proximal Femoral Focal Deficiency (PFFD) - Parvin Raji; Mohammad Reza Hadian (University of Social Welfare and Rehabilitation Sciences, 2008)
Proximal Femoral Focal Deficiency (PFFD) is a rare congenital defect with prevalence of one in 50000 to 200000 live births. It affects the proximal femur and frequently the acetabulum and may occurs unilaterally and/or bilaterally. The side effects of PFFD vary in patients. These include: limb length discrepancy, instability of the hip and knee joint, contractures of the hip and knee muscles, unequal level of the knees, short stature and associated anomalies. Usually, children with PFFD and their families are faced with many treatment decisions, both surgical and non- surgical. Therefore, the treatment of PFFD has always been a challenge for the specialists. In this report, a 3-years-old boy with PFFD with dysplasia of hip and acetabulum and femur shortness in both side and delay in motor milestones has been reported who was referred by physician to the faculty of rehabilitation for occupational therapy and rehabilitation treatment.